The Social Distancing- ID card - Anurag Singh; Shinde, Mahesh (Journal of Advanced Research in Public Policy and Administration, 2021)
The Sustainable Development Goals (SDGs) are collection of 17 global goals set by the United Nations General Assembly in 2015 for the year 2030. This paper shows how important to maintain the social distance in the current outbreak of COVID 19. In short, on the small scope a prototype is used to maintain social distance in social places like school, college, organizations and etc. This prototype will alert the user if someone is coming within the area specified. Using sensor, the user can maintain appropriate distance while working. How to cite this article: Singh A, Shinde M. The Social Distancing- ID card. J Adv Res Pub Poli Admn 2021; 3(1): 21-23.